LIVER ENZYMES IN TYPE-2 DIABETES MELLITUS PATIENTS - Pradeep Kumar Burubu; Ivvala Anand Shaker; Pawan Anilkumar Toshniwal; Seema Toshniwal; M.M. Suchitra; V.S. Kiranmayi; Brahma Reddy Malapati; Bidwe Santosh Eknath; Dussa Hemachandan; Lewin Wilson C; Barla Krishna; Aafrin Daruwala; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Diabetes is a strong-growing metabolic ailment across the globe. The occurrence ofdiabetes everywhere the world affects more than 8% of the global population. "Type 2 diabetes (T2D) isLiver Enzymes In Type-2 Diabetes Mellitus PatientsVol.31 No.04 (2024): JPTCP (1125-1132) Page | 1126a major public health concern distressing lots of people globally." "Nearly 70% of patients with type 2diabetes mellitus (T2DM) have a fatty liver."Aims and objectives: We aimed to detect the rise of liver enzymes and its association with Type-2diabetes mellitus associated with liver dysfunction. The aim of the study was to measure the level of liverenzymes.Material and methods: A case-control type of study was enrolled total of 60 age sex matchedsubjects, where subject were further categories into 30 type-II diabetic mellitus attendingEndocrinology outpatient of Sri Venkateswara Institute of Medical Sciences, Tirupati and 30healthy individuals of in and around of institution. A confirm diagnosis of type-II DM was based onstandard ADA criteria. Statistical analysis was done by using SPPS version 16.Results: A total of 60 subjects were assessed for liver profile and diabetic profiles. A data waspresented in mean and SD form. The mean age of participants was 46.77 ± 7.74. Blood sugar levels(fasting & PP2) and liver enzymes were significantly increased, while mean levels of protein fractionswere significantly decreases in cases as compared to controls (p